Joint Vibration Analysis in Patients with Articular Inflammation - Garcia, Alício Rosalino; Madeira, Miguel Carlos; Paiva, Guivaldo; Olivieri, Karina Andrea Novaes [UNESP] (My University, 2000)
The study of articular sounds using a computerized system (SonoPAK) in patients with temporomandibular disorders (TMD) of inflammatory origin revealed an increase of vibratory energy when compared to asymptomatic individuals. The following conclusions were reached: 1. The amount of vibratory energy registered in these patients ranged from 8.50 to 57.61 Hz. The major vibrations occurred in the middle of the mandibular opening cycle; 2. The mean vibratory energy measured at less than 300 Hz was between 5.70 and 48.64 Hz and at higher than 300 Hz was between 3.70 and 8.99 Hz; 3. The peak amplitude in the patients with inflammation ranged from 0.35 to 3.96 Pascal and the peak of frequency from 83.20 to 120.20 Hz.
Keywords: diagnostic agent; adolescent; adult; arthritis; comparative study; computer assisted diagnosis; female; human; joint characteristics and functions; male; mandible; middle aged; movement (physiology); pathophysiology; periarthritis; physiology; sound; synovitis; temporomandibular joint; temporomandibular joint disorder; vibration; Adolescent; Adult; Arthritis; Diagnosis, Computer-Assisted; Female; Humans; Male; Mandible; Middle Aged; Movement; Periarthritis; Range of Motion, Articular; Sound; Synovitis; Temporomandibular Joint Disk; Temporomandibular Joint Disorders; Vibration